The Epic and the Lyrical in Vadim Levanov’s Dramaturgy - Журчева, Татьяна (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2014)
The article is devoted to the correlation of epic and lyrical features in the plays by Vadim Levanov, one of the most interesting authors of the newest Russian dramaturgy. Special attention is given to the plays united in a historical diptych: The Life of the Holy Blessed Xenia of St. Petersburg and The Most Possibly Authentic and Plausible Biography of the Bloody Lady Darya Saltykova, a Moscow Hereditary Noblewoman.